A Bifactor Model of Intolerance of Uncertainty in Undergraduate and Clinical Samples: Do We Need to Reconsider the Two-Factor Model? - Shihata, S.; McEvoy, Peter; Mullan, Barbara (American Psychological Association, 2018)
The theorized role that intolerance of uncertainty (IU) plays in the acquisition, maintenance, and treatment of multiple emotional disorders underscores the importance of valid assessment tools. Research using the Intolerance of Uncertainty Scale-Short form (IUS-12) has conceptualized IU along 2 dimensions, namely, prospective IU and inhibitory IU. However, recent research has cast doubt on the separability of these dimensions. The aim of the current study was to evaluate the fit of competing measurement models of the IUS-12 in separate undergraduate (N = 506) and clinical (N = 524) samples. Unidimensional, correlated 2-factor, and bifactor models were tested using confirmatory factor analysis. The results of both studies supported a bifactor model consisting of a strong general IU factor. The general IU factor explained the majority of unique variance in the IUS-12, and suggested that a total score is generally appropriate for assessing IU. The general IU factor was most strongly and consistently associated with symptoms of multiple disorders. The inhibitory IU group factor was more weakly associated with most symptom measures in the clinical sample, but only with social phobia symptoms in the undergraduate sample. The prospective IU group factor was only separable from the general IU factor in the undergraduate sample, and did not explain unique variance in disorder symptoms.